The Pengaruh Model Reciprocal Teaching Terhadap Minat Baca Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas V SD IT Alief Mardhiyah Kabupaten Cirebon - Pandani, Ziah; Faridah Laily, Idah; Maufur, Syibli (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
The importance of interest in reading in learning Indonesian. The aim of this research is to determine the effect of the reciprocal teaching model on reading interest in Indonesian language subjects for fifth grade students at SDIT Alief Mardhiyah, Cirebon Regency. The population of this study was 23 class V students. The sample in this study amounted to 23 people. The sampling technique for this research uses a saturated sampling technique. The method used in this research is an experimental method in the form of Pre-Experimental Designs with the One-Group Pretest-Posttest Design type. Data collection uses observation and questionnaires. The data analysis techniques used in this research were normality test, homogeneity test and t test. The results of research using teacher activity observation sheets obtained a score of 100%, which is in the good category. The student reading interest questionnaire score was 71.1% and was included in the very strong category. There is an influence of the reciprocal teaching model on reading interest in Indonesian language subjects for fifth grade students at SDIT Alief Mardhiyah, Cirebon Regency, namely with a value of Sig. (0.000) < probability 0.05, so it can be concluded that Ha is accepted, meaning that there is an influence between the use of the reciprocal teaching model on reading interest in Indonesian language subjects for fifth grade students at SDIT Alief Mardhiyah, Cirebon Regency.